(untitled) (Ius Novum, 2024)
This study attempts to answer the question whether the assumptions and expectations of the legislators, as expressed in the 2015 amendment to criminal law concerning the penalty of restriction of liberty, have been fulfilled in judicial practice. Based on the analysis, it appears that the main goal of the reform has been achieved: namely, a significant reduction in the adjudication of the penalty of restriction of liberty with conditional suspension of execution in favour of non-custodial penalties. Consequently, the role of the penalty of restriction of liberty in criminal policy has significantly expanded; however, these changes have also had a negative outcome by increasing the use of unconditional imprisonment. This indicates that for some offenders, limiting the application of conditional suspension of penalty execution has led to a rise in the frequency of unconditional imprisonment. When analysing issues related to the adjudication and execution of the penalty of restriction of liberty, particular attention was drawn to the importance of accurately selecting this penalty in the form of an obligation to perform unpaid, supervised community service in specific cases, and the non-compliance in practice with the directive in Article 58 § 2a of the Polish Criminal Code. This led to an increase in the number of substitute imprisonment penalties ordered in place of the restriction of liberty penalty. Additionally, based on established data, serious concerns arise regarding the effectiveness of the penalty of restriction of liberty, as measured by recidivism rates. This is because it brings the penalty of restriction of liberty closer in effectiveness to unconditional imprisonment and significantly deviates from the effectiveness of other noncustodial penalties and measures.